2017
DOI: 10.1016/j.bbi.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Systemic TNF-α produces acute cognitive dysfunction and exaggerated sickness behavior when superimposed upon progressive neurodegeneration

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 70 publications
5
66
0
Order By: Relevance
“…The IL-1β experiment showed an interaction of disease and treatment (F 1,53 =5.42, p=0.0236) and ME7+saline and ME7+IL-1β animals were significantly different at 1 and 3 hours (p<0.05). As previously described (Hennessy et al, 2017), Bonferroni post-hoc analysis showed that ME7+TNF-α animals were significantly different from both NBH+TNF-α and from ME7+saline at 1 hour after a significant interaction of disease, treatment and time in 3-way ANOVA analysis (F=3.09, df 6,328, p<0.01).…”
Section: Lps Differentially Affects Working Memory In Vulnerable Animsupporting
confidence: 67%
See 1 more Smart Citation
“…The IL-1β experiment showed an interaction of disease and treatment (F 1,53 =5.42, p=0.0236) and ME7+saline and ME7+IL-1β animals were significantly different at 1 and 3 hours (p<0.05). As previously described (Hennessy et al, 2017), Bonferroni post-hoc analysis showed that ME7+TNF-α animals were significantly different from both NBH+TNF-α and from ME7+saline at 1 hour after a significant interaction of disease, treatment and time in 3-way ANOVA analysis (F=3.09, df 6,328, p<0.01).…”
Section: Lps Differentially Affects Working Memory In Vulnerable Animsupporting
confidence: 67%
“…Group sizes were as follows: NBH+saline (n=16), NBH+TNF (n=11), NBH+IL-1β (n=14), ME7+saline (n=20), ME7+TNF (n=12),ME7+IL-1β (n=12). Data pertaining to TNF-α originally published inHennessy et al, 2017, BBI, 10.1016/j.bbi.2016.09.011(Hennessy et al, 2017). Significant main effects and interactions are described in the main text.…”
mentioning
confidence: 99%
“…Nonetheless, the NLRP3 inflammasome, an enzyme complex responsible for cleavage and maturation of IL-1 is activated and influences amyloidosis and cognitive function in the APP/PS1 model of AD (Heneka et al 2012;Venegas et al 2017). We previously showed that microglia are 'primed' by primary neuropathology to produce exaggerated acute neuroinflammatory responses to secondary acute stimulation with bacterial endotoxin (Cunningham et al 2005), double stranded RNA (Field et al 2010) and inflammatory cytokines IL-1 and TNFα (Hennessy et al 2017). Such switching of glial phenotypes may release the restraint on microglia during neurodegeneration to induce a more classically activated microglial phenotype which may be an important component of the contribution of systemic inflammation to disease-associated outcomes such as neuronal damage and cognitive decline Holmes et al 2009;Semmler et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is evidence to show that conditions such as sepsis and hip fracture cause changes in inflammatory markers [177,178], however, there is little evidence about whether delirium self-propagates. Some animal model data in delirium suggests that there might be a direct impact of inflammatory markers on brain dysfunction [179]. To our knowledge there was no published relationship between tumor markers and neurological brain dysfunction.…”
Section: Discussionmentioning
confidence: 80%